Genetic data support the relict and native status of Styrax officinalis L. (Styracaceae) in Italy - Parducci, Laura; Ribeiro, Maria Margarida; Nota, Kevin; Nobile, Alessandro; De Santis, Simone; Diamantino, Tatiana; Drouzas, Andreas D.; Aplada, Eirini; Hirota, Shun K.; Suyama, Yoshihisa; Spada, Francesco (Frontiers in Ecology and Evolution, 2025)
IntroductionThe woody angiosperm Styrax officinalis L., primarily occurring in the Near East and South-eastern Europe, has been historically considered a human introduction in the Italian Peninsula.MethodsTo challenge this assumption, we conducted a genetic analysis on a comprehensive sample of individuals across its range, utilizing chloroplast and nuclear microsatellites as well as a genome-wide single-nucleotide polymorphism (MIG-seq) sequencing approach.ResultsAnalysis of 351 individuals revealed clear genetic structure across the species’ range. Most Italian populations form a distinct nuclear genetic cluster, suggesting long-term isolation, while three populations show signs of admixture with Cypriot individuals. Although one rare chloroplast haplotype was unique to Italy, widespread eastern haplotypes were entirely absent from the peninsula, which does not support the hypothesis of a recent human-mediated introduction.DiscussionThe results largely support the indigenous nature of the species in the Italian Peninsula, rejecting the notion of recent human introduction, and elevate S. officinalis to the status of a local relict, probably representing a component of the Late Neogene warm-temperate vegetation in Southern Paleo Europe.